OPPORTUNITIES FOR DEVELOPING GREEN FINANCE IN UZBEKISTAN (World Bulletin of Social Sciences, 2024)
Green finance, a critical enabler for achieving sustainability and combating climate change, holds immense potential for Uzbekistan’s economic and environmental future. As a nation undergoing rapid economic reforms, Uzbekistan faces growing environmental challenges such as air pollution, water scarcity, and soil degradation. Integrating green finance mechanisms can mobilize resources for renewable energy, sustainable agriculture, and eco-friendly infrastructure. This article explores the current state of green finance in Uzbekistan, evaluates existing policies and practices, and identifies key opportunities for growth. The role of international partnerships, technological advancements, and regulatory reforms in advancing green finance is also analyzed. By leveraging these opportunities, Uzbekistan can position itself as a leader in sustainable development in Central Asia.
Keywords: Green finance, Uzbekistan, sustainable development, renewable energy, climate change, eco-friendly infrastructure, environmental sustainability, financial instruments